If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Log(2)(14 + -6x) = 2log(2)(x + -1) + 1 Reorder the terms for easier multiplication: 2goL(14 + -6x) = 2log(2)(x + -1) + 1 (14 * 2goL + -6x * 2goL) = 2log(2)(x + -1) + 1 (28goL + -12goxL) = 2log(2)(x + -1) + 1 Reorder the terms: 28goL + -12goxL = 2glo * 2(-1 + x) + 1 Reorder the terms for easier multiplication: 28goL + -12goxL = 2 * 2glo(-1 + x) + 1 Multiply 2 * 2 28goL + -12goxL = 4glo(-1 + x) + 1 28goL + -12goxL = (-1 * 4glo + x * 4glo) + 1 28goL + -12goxL = (-4glo + 4glox) + 1 Reorder the terms: 28goL + -12goxL = 1 + -4glo + 4glox Solving 28goL + -12goxL = 1 + -4glo + 4glox Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '4glo' to each side of the equation. 28goL + 4glo + -12goxL = 1 + -4glo + 4glo + 4glox Reorder the terms: 4glo + 28goL + -12goxL = 1 + -4glo + 4glo + 4glox Combine like terms: -4glo + 4glo = 0 4glo + 28goL + -12goxL = 1 + 0 + 4glox 4glo + 28goL + -12goxL = 1 + 4glox Add '-4glox' to each side of the equation. 4glo + 28goL + -4glox + -12goxL = 1 + 4glox + -4glox Reorder the terms: 4glo + -4glox + 28goL + -12goxL = 1 + 4glox + -4glox Combine like terms: 4glox + -4glox = 0 4glo + -4glox + 28goL + -12goxL = 1 + 0 4glo + -4glox + 28goL + -12goxL = 1 Reorder the terms: -1 + 4glo + -4glox + 28goL + -12goxL = 1 + -1 Combine like terms: 1 + -1 = 0 -1 + 4glo + -4glox + 28goL + -12goxL = 0 The solution to this equation could not be determined.
| y=1x-3 | | y=-1x-3 | | 2.7x+4.7=2.3x+9.54 | | 9q-25=4q | | 1.3y-14.2=11.3-3.8y | | 4v=v-18 | | 8z=4z-12 | | 0.8x-9=3x+13 | | 6z=35-z | | 2x-(9-3(4x-7))=26 | | 6-3x=4(x+2) | | 5-7x=92-28x | | (3x+2)-(2x-5)=0 | | 2x-7(x-3)=26 | | 5x+4-3(2x-1)=8-(7x-1)x | | 2x-3=10x-37 | | 5(x+2)-3(x-1)=12 | | 101-6x=2x+5 | | 6-x^2-(3-2x)=0 | | 6(3d-7)= | | 2(7c+1)= | | -13x-6x=8-9x | | x-2/3=2x+7/5 | | (5w+6)(5w-6)=0 | | -3.5t^2+4.7t-2.9=0 | | 8y-14=6 | | 6x-3x=3x | | 8y-14=-6 | | x+73=x-4 | | (2(x^3-2x+4)-(x-3)(x^2+5x-4))(3-2x)= | | 3(n+4)+3(n+4)= | | x+2/2+x+3/3=2x+5/4 |